Teacher's corrective feedback and students' uptake in ESL classrooms in a public secondary school in Malaysia / Ainatul Basirah Othman - Othman, Ainatul Basirah (Faculty of Education, 2013)
The study aimed to investigate corrective feedback and uptake that occurs in ESL classrooms in a public secondary school in Malaysia. It looked at the kind of corrective feedback that teachers give to students when they made spoken errors as well students' response or uptake following the given corrective feedback. The study was sparked by similar studies in the field particularly the one done by Lyster and Ranata (1997) which indicates that certain types of corrective feedback is more effective in eliciting students' uptake. The study involved 174 Form 3 students from four classes; two classes of the higher English proficiency and another two classes of the lower English proficiency. The researcher observed 12 hours of English lessons in order to find out the kind of corrective feedback which teacher employed as well as students' uptake following it. The researcher also interviewed the two English teachers observed in the classroom observation in order to find out more on their corrective feedback practice. The study found recast to be the most preferred corrective feedback and also the least likely to lead to students' uptake.Students were most likely to produce uptake following metalinguistic feedback, elicitation and repetition. Metalinguistic feedback was also found to be most effective in leading towards student-generated repair as opposed to teachergenerated repair. The interview revealed that teacher's choice of corrective feedback was not guided by formal knowledge on corrective feedback and uptake but by instinct and practicality. The findings were followed with discussion on implications as well as several recommendations.